EXPRESSIVE SPEECH ACTS IN POLITICAL RAP BATTLE - Nadivia Nazla Syafa; Linda Eka Pradita; Mursia Ekawati (Jurnal Ilmiah Bina Bahasa, 2025)
Political rap battles have evolved into a form of digital communication that combines entertainment with socio-political criticism through the strategic use of expressive speech acts. This is important to publish because it represents a transformation in contemporary political communication that utilizes popular culture to reach a wide audience, especially the younger generation who tend to be apathetic towards formal politics. Although the popularity of political rap battles in Indonesia continues to rise, a significant gap remains in understanding their linguistic characteristics and pragmatic functions as a medium of digital political communication. This study examines the forms and functions of expressive speech acts in four popular rap battle videos from the YouTube channel SkinnyIndonesia24, employing a descriptive-analytical qualitative method. Data consisting of 80 utterances were analyzed based on Austin-Searle's speech act theory to identify six expressive categories: criticism (50 utterances), pride (22 utterances), anger (2 utterances), disappointment (2 utterances), praise (2 utterances), and apology (2 utterances). The findings indicate that expressive speech acts function as rhetorical strategies to convey ideological messages through the use of irony, hyperbole, and sarcasm. This study has important implications for the development of digital literacy and the understanding of contemporary Indonesian political communication, demonstrating that rap battles are a legitimate and influential space for political articulation in shaping public discourse.